Pattern of distal radius fracture in malaysian children - Asim, A.M.; Noor Fadzilah, R.; Shanmugam, Rukmanikanthan; Saw, A. (Malaysian Medical Association, 2012)
INTRODUCTION: The distal radius is the most common fracture site in children, but local information on the fracture pattern, mechanism of injury and socio-demographic characteristics of the fracture is lacking.